2015
DOI: 10.3945/jn.115.217406
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Butyrate Decreases Postweaning Diarrhea by Modulating Intestinal Permeability and Changing the Bacterial Communities in Weaned Piglets1–3

Abstract: Collectively, our results support an important role for SB in improving performance and decreasing diarrhea incidence in weaned piglets by modulation of intestinal permeability and the bacterial communities in the ileum and colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
191
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(217 citation statements)
references
References 42 publications
17
191
2
7
Order By: Relevance
“…Wang et al 34 have observed that sodium butyrate induced increase in gene expression and protein content of claudin-1 in the intestinal epithelial cell line IEC, possibly due to a higher level of interaction between the SP1 transcription factor, and its promoter. Additionally, Huang et al 70 reported that the decrease in paracellular intestinal permeability, as measured by lactulose/mannitol assay in urine, is associated with increased expression of occludin in jejunum and colon segments of newborn pigs after butyrate treatment in combination with antibiotics. The authors suggested that this effect on intestinal function was probably due to an anti-inflammatory action of this SCFA since the TNF-a concentration was lower in the mucosa of animals receiving treatment with butyrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 34 have observed that sodium butyrate induced increase in gene expression and protein content of claudin-1 in the intestinal epithelial cell line IEC, possibly due to a higher level of interaction between the SP1 transcription factor, and its promoter. Additionally, Huang et al 70 reported that the decrease in paracellular intestinal permeability, as measured by lactulose/mannitol assay in urine, is associated with increased expression of occludin in jejunum and colon segments of newborn pigs after butyrate treatment in combination with antibiotics. The authors suggested that this effect on intestinal function was probably due to an anti-inflammatory action of this SCFA since the TNF-a concentration was lower in the mucosa of animals receiving treatment with butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that this effect on intestinal function was probably due to an anti-inflammatory action of this SCFA since the TNF-a concentration was lower in the mucosa of animals receiving treatment with butyrate. 70 The mechanism of action of sodium butyrate on cellular expression of claudin-1 or other structural proteins of TJ is still unknown; however, it may also be related to its action as an inhibitor of the HDAC enzyme. Sodium butyrate causes hyperacetylation of histones by inhibiting histone affinity with DNA and thus increases the exposure of regions for transcription of certain genes.…”
Section: Discussionmentioning
confidence: 99%
“…Suplementacja diety maśla-nem sodu zwiększa ekspresję okludyny, czyli białka modelującego przepuszczalność jelitową. To powoduje wzmocnienie integralności nabłonka jelit i przyspiesza proces gojenia się ran (18,28). Zastosowanie maślanu sodu wpływa na zmniejszenie udziału związanego z procesem zapalnym czynnika martwicy nowotworu TNF-α o 69%.…”
Section: Ryc 2 Mechanizm Działania Kwasu Organicznego Na Komórkę Baunclassified
“…Zauważono także spadek populacji bakterii z rodzaju Clostridium w okrężnicy, co ograniczyło często-tliwość występowania biegunek u odsadzonych prosiąt (tab. 1) (18). Ponadto, maślan sodu indukuje ekspresję niektórych peptydów przeciwbakteryjnych (HDP -Host Defence Peptides) w komórkach nabłonkowych jelit.…”
Section: Ryc 2 Mechanizm Działania Kwasu Organicznego Na Komórkę Baunclassified
“…Phy and Provenza (1998) illustrated that small ruminants preferred pelletized fermentable concentrate diets supplemented with sodium bicarbonate. Dietary sodium butyrate decreased digestive tract permeability and facilitated considerable alterations in intestinal microbial population (Huang et al, 2015) in addition to reducing colonic inflammation (Wirtz and Neurath, 2007).…”
Section: Introductionmentioning
confidence: 99%